Eksistensi Gubernur Dalam Konteks Desentralisasi Dan Otonomi Daerah Di Indonesia - M. Syaiful Rachman; Ferdy Ferdian (Jurnal Rechten : Riset Hukum dan Hak Asasi Manusia, 2019)
This paper will describe Governor existence as representative of National Government in local region and as implementer of regional autonomy. Analytical tools for this paper is Law of The Republik Indonesia No.22 of 1999 about Local Government and its revision in Law of The Republik Indonesia No. 32 of 2004 and some of Government Regulation which are following of both Law. Focus of this paper are (1) Roles of existence and functions of Local Government Province and Governor as an actor of decentralization, deconcentration and medebewind; (2) Roles and functions Governor as representative of National Government in Local Region. At last, I give some recommendation for strengthening position, role and authority for Governor as representative National government in local region.